PERAN MAJELIS TALIM BAROKATUL MUSTHOFA SEBAGAI PENDIDIKAN ISLAM NON-FORMAL DALAM MENINGKATKAN PEMAHAMAN KEAGAMAAN PADA MASYARAKAT DI KAMPUNG CANGKRANG - Abdul Aziz; Suhendra; Yono (KOLONI, 2022)
This research is entitled "The Role of the Barokatul Musthofa Ta'lim Council as Non-Formal Islamic Education in Improving Religious Understanding in the Community in Cangkrang Village". This study aims to determine the role of the Barokatul Musthofa ta'lim assembly in an effort to increase religious understanding in the community in Cangkrang Village, Cikarawang Village. The method used in this study is a qualitative method, while the data collection tools include; interviews, observations and documentation. From the results of research conducted by researchers on the Barokatul Musthofa ta'lim assembly, it can be seen that the Barokatul Musthofa ta'lim assembly as a non-formal Islamic educational institution located in the midst of society has contributed significantly to the development of religious understanding in the community in Cangkrang Village, Cikarawang Village. In terms of worship, we can see from the narratives of the members of the congregation that the role of the Barokatul Musthofa ta'lim assembly made the members of the congregation more diligent and obedient in worship, then in terms of faith, the Barokatul Musthofa ta'lim assembly also had a positive impact on the congregation, such as making them more stable in faith and get peace of mind. Keyword: Role, Ta'alim Council, Religious Understanding.